2023
DOI: 10.3390/ijms24076760
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Linking PPARG Genetic Variants with Periodontitis and Type 2 Diabetes Mellitus in a Brazilian Population

Abstract: The peroxisome proliferator-activated receptor gamma (PPARG) gene encodes a transcription factor involved in the regulation of complex metabolic and inflammatory diseases. We investigated whether single nucleotide polymorphisms (SNPs) and haplotypes of the PPARG gene could contribute with susceptibility to develop periodontitis alone or together with type 2 diabetes mellitus (T2DM). Moreover, we evaluated the gene–phenotype association by assessing the subjects’ biochemical and periodontal parameters, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In addition to bone-related effects, the polymorphism of this gene has been shown to impact other systems significantly. Cirelli et al demonstrated that the wild-type allele of rs1151999 significantly reduced the risk of hyperglycemia, hyperlipidemia, and obesity even after adjustments for age, sex, and smoking status in a Brazilian population [ 36 ]. Moreover, the rs1151999 SNP was associated with protection against Alzheimer’s disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bone-related effects, the polymorphism of this gene has been shown to impact other systems significantly. Cirelli et al demonstrated that the wild-type allele of rs1151999 significantly reduced the risk of hyperglycemia, hyperlipidemia, and obesity even after adjustments for age, sex, and smoking status in a Brazilian population [ 36 ]. Moreover, the rs1151999 SNP was associated with protection against Alzheimer’s disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%